Left ventricle hydatid cyst of heart removed under cardiopulmonary bypass: anesthesia management - Pawar, Dharamsingh Kishanrao; Ramtani, Umesh; Varshney, Sauabh; Mankar, Shital N.; Deshmukh, Durgesh G. (International Journal of Research in Medical Sciences, 2017)
Hydatid cyst uncommon in heart, echinococcosis is endemine in our country. Hydatid cyst in a heart may causes disturbances in conducting system, Pericarditis congestive cardiac failure. The surgery and anesthetic management become very challenging in this case. We are describing the successful management of such a case of left ventricle hydatid cyst remove under cardio pulmonary bypass in a middle age female.